Association of Natural Killer Cell Ligand Polymorphism HLA–C Asn80Lys With the Development of Anti‐SSA/Ro–Associated Congenital Heart Block. Issue 11 (17th October 2017) - Ainsworth, Hannah C.; Marion, Miranda C.; Bertero, Tiziana; Brucato, Antonio; Cimaz, Rolando; Costedoat‐Chalumeau, Nathalie; Fredi, Micaela; Gaffney, Patrick; Kelly, Jennifer; Levesque, Kateri; Maltret, Alice; Morel, Nathalie; et al.
Abstract : Objective: Fetal exposure to maternal anti‐SSA/Ro antibodies is necessary but not sufficient for the development of autoimmune congenital heart block (CHB), suggesting that other factors, such as fetal genetic predisposition, are important. Given the previously described association between major histocompatibility complex alleles and CHB risk, we undertook the present study to test the hypothesis that a variant form of HLA–C Asn80Lys, which binds with high affinity to an inhibitory killer cell immunoglobulin‐like receptor (KIR) and thus renders natural killer (NK) cells incapable of restricting inflammation, contributes to the development of CHB. Methods: Members of 192 pedigrees in the US and Europe (194 cases of CHB, 91 unaffected siblings, 152 fathers, 167 mothers) and 1, 073 out‐of‐study controls were genotyped on the Immunochip single‐nucleotide polymorphism microarray. Imputation was used to identify associations at HLA–C Asn80Lys (Asn, C1; Lys, C2) and KIR. Tests for association were performed using logistic regression. McNemar's test and the pedigree disequilibrium test (PDT) were used for matched analyses between affected and unaffected children. Results: Compared with out‐of‐study controls of the same sex, the C2 allele was less frequent in the mothers (odds ratio [OR] 0.63, P = 0.0014) and more frequent in the fathers (OR 1.40, P = 0.0123), yielding a significant sex‐by‐C2 interaction ( P = 0.0002). The C2 allele was more frequent in affected siblings than in unaffected siblings (OR 3.67, P = 0.0025), which was consistent with the PDT results ( P = 0.016); these results were observed in both sexes and across the US and European cohorts. There was no difference in the frequency of the inhibitory KIR genotype (KIR AA) between affected and unaffected children ( P = 0.55). Conclusion: These data establish C2 as a novel genetic risk factor associated with CHB. This observation supports a model in which fetuses with C2 ligand expression and maternal anti‐SSA/Ro positivity may have impaired NK cell surveillance, resulting in unchecked cardiac inflammation and scarring.